Castlebank Street and the origins of the Bishop's house/Partick Castle. Issue 1 (March 2019) - Green, Kenneth; Whitehouse et al., Nickie J
Abstract : Excavations at Castlebank Street, Partick between the Clyde and the Kelvin Rivers revealed some archaeological features. The earliest was a Roman/Iron Age ditch, dated to the second to third century AD. Medieval activity on the site included a large north-east/south-west oriented ditch with a culvert and a slightly later substantial stone wall. In addition, a stone-lined well was located and a small ditch with associated features in the north of the excavated area. These features spanned the beginning of the eleventh to the end of the fourteenth century. A limited range of material culture, mainly medieval and later medieval local pottery, with some glass and animal bone was associated with the fills of the larger ditch, culvert and wall. Historical research revealed a complex history surrounding the establishment of the Bishop of Glasgow's country estate and manor house (the early castle?) and its subsequent demolition. However, it has been difficult to match the archaeological evidence with the historical documentation mainly due to nineteenth century use of the area for a foundry and laundry, as well as the insertion of South Orchard Street, which did much to obliterate evidence from earlier periods.